The impact of Colombia's pension and health insurance systems on informality - Valentina Calderón-Mejía; Ioana E. Marinescu (Institute for the Study of Labor (IZA), 2012)
Social protection systems in developing countries are typically composed of a bundle of benefits, the major ones being health insurance and pensions. Benefit bundling may increase informality and decrease welfare. Indeed, if some of the benefits are valued at substantially less than their cost, workers may choose to forego all benefits, even though some other benefits are valued at or above their cost. We examine the impact of benefit bundling using a series of Colombian reforms. The key reform is the unification of the payment systems for health and pension, which made it more difficult to contribute differently to the one plan versus the other. Using the progressive roll-out of the unified payment system by firm size, we show that benefit bundling increases both full formality and full informality by about 1 percentage point. The increase in full formality is concentrated among salaried workers in small to medium firms, while the increase in full informality is concentrated among independent workers.
urn:nbn:de:101:1-201207126737
Keywords: I11; I18; O17; 330; informal sector; pensions; health insurance; social protection; Colombia; Soziale Sicherung; Gesetzliche Rentenversicherung; Gesetzliche Krankenversicherung; Leistungsbündel; Wirkungsanalyse; Informeller Sektor; Schätzung; Kolumbien